CAUSE OF STRESS AMONG PRIVATE BANK EMPLOYEES: AN ANALYSIS - M K, Manjunatha; Renukamurthy, T.P. (International Journal of Research -GRANTHAALAYAH, 2020)
Purpose of this study is examining the cause of stress among selected private banking employees. Stratified sampling method was used to carry out the data collection. For this employee of various private banks were chosen. A questionnaire with 12 items with dichotomous (Yes-1, NO-2) were developed and tested for reliability and prior to the distribution of questionnaire. 253 respondents were selected from various private banks in Mysore district, Karnataka state India. The survey questionnaire was sent via email, requesting to complete it. The questionnaire includes 11 demographic information’s and statements to measure. Chi-Square analysis was carried out to examine the cause of stress among employee using SPSS21. We found that designations have significant influence on employee and The other factors of do not have any significant influence on employee. Therefore we concluded that in private banks demographic variable such as designation creates stress in all aspects. Future research should consider a larger sample from leading sectors where job natures are similar. Analysis should be more rigorous, where Amos could be used for analysis.